2007
DOI: 10.1289/ehp.9022
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Childhood Leukemia in Churchill County, Nevada

Abstract: BackgroundSixteen children diagnosed with acute leukemia between 1997 and 2002 lived in Churchill County, Nevada, at the time of or before their illness. Considering the county population and statewide cancer rate, fewer than two cases would be expected.ObjectivesIn March 2001, the Centers for Disease Control and Prevention led federal, state, and local agencies in a cross-sectional, case-comparison study to determine if ongoing environmental exposures posed a health risk to residents and to compare levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 45 publications
2
44
1
Order By: Relevance
“…In the German Environmental Survey III of 1998, median urinary total arsenic levels in 4052 adults varied with seafood intake and were approximately two-fold lower than those for NHANES 2003(Schulz et al, 2007. Higher mean or median (Calderon et al, 1999;Meza et al, 2004;Valenzuela et al, 2005;Josyula et al, 2006;Rubin et al, 2007), as well as for other areas of the world (Ahsan et al, 2000;Aposhian et al, 2000;Caceres et al, 2005;Sun et al, 2007), that were known to have higher levels of arsenic in their drinking water. Median and mean total urinary arsenic levels for residents in some districts in Bangladesh have been reported to be about 50-fold higher than the respective levels in NHANES 2003(Ahsan et al, 2000Chowdhury et al, 2003) and geometric mean levels were about 70-fold higher for residents of Inner Mongolia, China (Sun et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…In the German Environmental Survey III of 1998, median urinary total arsenic levels in 4052 adults varied with seafood intake and were approximately two-fold lower than those for NHANES 2003(Schulz et al, 2007. Higher mean or median (Calderon et al, 1999;Meza et al, 2004;Valenzuela et al, 2005;Josyula et al, 2006;Rubin et al, 2007), as well as for other areas of the world (Ahsan et al, 2000;Aposhian et al, 2000;Caceres et al, 2005;Sun et al, 2007), that were known to have higher levels of arsenic in their drinking water. Median and mean total urinary arsenic levels for residents in some districts in Bangladesh have been reported to be about 50-fold higher than the respective levels in NHANES 2003(Ahsan et al, 2000Chowdhury et al, 2003) and geometric mean levels were about 70-fold higher for residents of Inner Mongolia, China (Sun et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…In this sense, studies have been carried out to evaluate both toxic and carcinogenic effects of these products (Flores et al, 2004;Rubin et al, 2007;Shafer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the indiscriminate practice has caused environmental impacts on the soil and water in a drastic way, which is sometimes difficult to measure. In this sense, some studies have demonstrated the toxic and carcinogenic effects of the plaguecides, especially those used in agriculture, which would contain organochlorate and pyrethroids, today forbidden in most developed countries, as well as in those in development (Flores et al, 2004;Rubin et al, 2007;Shafer et al, 2005). Currently, the so-called second-generation insecticides have proved to be more efficient and less toxic (Tingle et al, 2003).…”
Section: Introductionmentioning
confidence: 99%